Analysis of the Engagement Characteristic of the Improved Marine Wet Multi-plate Clutch - Zhu Yongxiang (Jixie chuandong)
In order to further the engagement characteristics of marine wet multi-plate clutch for accurate analysis and lay the foundation for the subsequent optimal design of marine clutch.Taking the marine wet clutch as the research object,based on the isothermal design,through the engagement process to determine the optimal pressure and improve the traditional pressure distribution model.Finally,a method for calculating the marine wet multi-plate clutch engagement characteristics is obtained.The results indicate that,based on the optimal pressure conditions required time for wet multi-plate clutch driving,driven disk angular velocity reached the speed is significantly less than the linear pressure,and friction work generated in the period is significantly less than the friction work generated by the linear pressure conditions.The wet type clutch-operating force change obtained by using pressure distribution has differences,and the engagement force of the operation after the correction is less than the conventional model,the engagement with the engagement pressure of the operating force is linear.There was no direct link between the actual and the effective radius of the wet clutch engagement pressure,but find that the new pressure is greater than the traditional model of distribution model in the calculation process.